Proximate, minerals, vitamins, and antinutrients and their correlations in the leaves of Senecio biafrae accessions - Baiyeri, Samuel (Journal of Agricultural Sciences (Belgrade), 2023)
Micronutrient malnutrition is a global challenge of both the elites and the resource-poor. There are promising opportunities for combating it through the consumption of neglected and under-utilized leafy green vegetables. Senecio biafrae is an underutilized and nutrient-dense green leafy vegetable with huge nutritional and health potentials that have remained under-exploited. It has received very limited research and funding attention. The aim of this research was to evaluate the proximate, minerals vitamins, anti-nutrients and their correlations among the accessions of this veggie. Leaf samples of the accessions were collected and assayed through standard biochemical methodologies.  Results showed that the accessions differed significantly (p
Keywords: Nutrient-dense; leafy vegetable; Senecio biafrae; minerals; vitamins; proximate; anti-nutrients; micronutrients